ANALISIS EFISIENSI PASAR MODAL INDONESIA BENTUK LEMAH DI BURSA EFEK INDONESIA PERIODE 2009-2013 - B11111102, TUTI MAISAROH (Jurnal Manajemen Update, 2015)
The hypothesis of weak form efficiency contends that there is no correlation instock prices due to security price movement is considered to be random. This study aimsto analyze weak form efficient market hyphotesis in Indonesian Stock Exchange (ISE).This study uses weekly stock price data of 21 companies included in LQ-45 Index duringthe 2009-2013. Sample is determined based upon purposive sampling technique.Collected data is then analyzed employing serial correlation and run test. Serialcorrelation test aims to measure the relationshipin stock prices while run test use fortesting the randomness of changes in stock prices. Results from this study period of 2009-2013 show that the Indonesiancapital market is efficient in the weak form. It meanssecurities movement have random walk pattern and independent.Keywords: Weak Form Efficient Market, Run Test, Serial Correlation Test And TheIndonesian Stock Exchange (ISE)